The Effect of a Structured Pre-Briefing Simulation Session on Medical Students’ Competency - Darwish, Enas; Jaradat, Ahmed; Ibrahim, Namaa; Ghalib, Kanz; Khonji, Sara; Gutierrez, Ruel; Garadah, Taysir (Jordan Medical Journal, 2023)
Background: The application of medical simulation as a teaching tool in medical education is mounting. Although pre-briefing is the introductory phase of the simulation process, its structure and role in medical education have not been well studied. Objective: To study the effect of a structured pre-briefing using concept mapping on medical students’ competency performance and clinical judgment. Methods: This study included 84 fifth-year medical students. Students were divided into two groups: the interventional group included 44 students who received structured pre-briefing (traditional pre-briefing plus concept mapping) and the control group of 40 who students received traditional pre-briefing. The students’ clinical competency was assessed using the Creighton Competency Evaluation Instrument (C-CEI) in addition to the pre-briefing assessment questionnaire filled out by the students at the end of the session. The mean difference ± SD between the two groups was assessed using a student’s t-test. The correlation between the outcomes was calculated using Pearson’s correlation coefficient analysis. Results: The competency performance score and clinical judgement scores were significantly higher in the interventional group than the control group, with a highly significant p-value of 0.000. In addition, the interventional group had a better perception of the pre-briefing experience than the control group, with a p-value of 0.000. However, there was no correlation between the C-CEI score and the students’ pre-briefing assessment questionnaire score. Conclusion: Structured pre-briefing using concept mapping significantly enhances medical students’ competency performance, clinical judgment, and perceptions of pre-briefing. It enables the learners to reflect on their previous experience and anticipate the plan of management more effectively.